2014
DOI: 10.1021/ja501777r
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Substrate Preferences for Photochemical Heterolysis Arise from Conical Intersection Control

Abstract: Heterolytic bond scission is a staple of chemical reactions. While qualitative and quantitative models exist for understanding the thermal heterolysis of carbon-leaving group (C-LG) bonds, no general models connect structure to reactivity for heterolysis in the excited state. CASSCF conical intersection searches were performed to investigate representative systems that undergo photoheterolysis to generate carbocations. Certain classes of unstabilized cations are found to have structurally nearby, low-energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 49 publications
5
57
1
3
Order By: Relevance
“…[39,40] As ar esult,t he fluorenyl carbocation has al ow-energy excited state and ah igh-energy ground state. The corresponding potential-energy surfaces are located in close proximity and this can lead to productivep hotoheterolysis through conicali ntersection, as recently postulated by Winter et al [41] Lukemana nd co-workers showed uncaging of 2,7-disubstituted-9-fluorenol acetate by irradiation at l = 300 nm. [42] Fluorene quaternary ammonium derivatives have also been used as ap hotobase to releasef ree tertiary amines.…”
Section: Fluorened Erivatives As Ppgsmentioning
confidence: 58%
“…[39,40] As ar esult,t he fluorenyl carbocation has al ow-energy excited state and ah igh-energy ground state. The corresponding potential-energy surfaces are located in close proximity and this can lead to productivep hotoheterolysis through conicali ntersection, as recently postulated by Winter et al [41] Lukemana nd co-workers showed uncaging of 2,7-disubstituted-9-fluorenol acetate by irradiation at l = 300 nm. [42] Fluorene quaternary ammonium derivatives have also been used as ap hotobase to releasef ree tertiary amines.…”
Section: Fluorened Erivatives As Ppgsmentioning
confidence: 58%
“…52 A recent computational study performed in our lab suggested the hypothesis that photoheterolysis reactions may be under conical intersection control. 53 That is, photoheterolysis of C-LG (carbon-leaving group) bonds to generate ion pairs 54 may be favored if the ion pair has access to a nearby productive conical intersection that provides an efficient channel for the excited state of the photoprecursor to decay to the ground-state ion pair. Because conical intersections are challenging to compute, we further suggested using the vertical energy gap of the carbocation to its first excited state as a simple predictor of a nearby conical intersection (CI).…”
mentioning
confidence: 99%
“…Winter and co-workers reported that some unstabilized carbocations have been found to have structurally nearby, low-energy conical intersections that are often favored for photochemical heterolysis, whereas some stabilized carbocations have been found to have high-energy, unfavorable conical intersections, which may be favored for thermal heterolysis. 50 For the formation of the carbocation intermediates in Scheme 2, the carbocation intermediate formed by the cleavage of the O 5 −C 6 bond could be considered unstabilized carbocations, so the cleavage of the O 5 −C 6 bond may be a photo-heterolysis control process rather than a thermal heterolysis process. 50 Therefore, the protonation of excited state β-LA may directly help induce the cleavage of the O 5 −C 6 bond and is hence proposed as being the predominant pathway (as shown in Scheme 2).…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
“…50 For the formation of the carbocation intermediates in Scheme 2, the carbocation intermediate formed by the cleavage of the O 5 −C 6 bond could be considered unstabilized carbocations, so the cleavage of the O 5 −C 6 bond may be a photo-heterolysis control process rather than a thermal heterolysis process. 50 Therefore, the protonation of excited state β-LA may directly help induce the cleavage of the O 5 −C 6 bond and is hence proposed as being the predominant pathway (as shown in Scheme 2).…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%